2011
DOI: 10.1590/s0102-86502011000500003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of broccoli extract on biodistribution and labeling blood components with 99mTc-GH

Abstract: PURPOSE: People consume vegetables without the knowledge of the side effects of the biological and chemical contents and interactions between radiopharmaceuticals and herbal extract. To this end, current study is focused on the effects of broccoli extract on biodistribution of radiolabeled glucoheptonate (99mTc-GH) and radiolabeling of blood components. METHODS: GH was labeled with 99mTc. Quality control studies were done utilizing TLC method. Biodistribution studies were performed on male rats which were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The procedure used for HPLC for broccoli extract was similar to that reported in other studies 19 . A low pressure gradient HPLC system (LC-10ATvp quaternary pump, SPD-10A/V UV detector, RF-10AXL Fluorescence detector, RAD501 single channel analyzer, a syringe injector equipped with a 1 mL loop and 7-µm VP 250/21 Nucleosil 100-7 C18 column (MachereyNagel)) was used for the analytical experiments.…”
Section: High Performance Liquid Chromatography (Hplc)mentioning
confidence: 88%
See 1 more Smart Citation
“…The procedure used for HPLC for broccoli extract was similar to that reported in other studies 19 . A low pressure gradient HPLC system (LC-10ATvp quaternary pump, SPD-10A/V UV detector, RF-10AXL Fluorescence detector, RAD501 single channel analyzer, a syringe injector equipped with a 1 mL loop and 7-µm VP 250/21 Nucleosil 100-7 C18 column (MachereyNagel)) was used for the analytical experiments.…”
Section: High Performance Liquid Chromatography (Hplc)mentioning
confidence: 88%
“…A similar procedure to that for the extraction of broccoli has been applied as described previously 19 . Broccoli was purchased from local market, dried at room temperature and powdered.…”
Section: Extraction Of Broccolimentioning
confidence: 99%
“…Data have demonstrated the effects of synthetic and natural drugs on this radiolabeling process (Mousinho et al, 2008;Holanda et al, 2009;Bustani et al, 2009;Rocha et al, 2009;De et al, 2009;Cekic et al, 2011;Souza et al, 2011). In consequence, the labeling of blood constituents with 99m Tc has been used as an in vitro assay to screening effects of synthetic or natural products that could have actions related to the band-3 and calcium channels or antioxidant/oxidant properties.…”
Section: +2mentioning
confidence: 99%
“…In one case report, 99m Tc RBCs were used to localize intrathoracic bleeding [24]. Authors reported that synthetic and natural medications might alter the bioavailability of radiopharmaceuticals [25,26], as well as the radiolabeling of blood constituents [25,[27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%